2010
DOI: 10.1016/j.jacc.2009.12.074
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Myocardial Fibrosis Quantification by Histopathology and Magnetic Resonance Imaging in Patients With Severe Aortic Valve Disease

Abstract: The amount of MF, either by histopathology or by ce-MRI, is associated with the degree of left ventricular functional improvement and all-cause mortality late after aortic valve replacement in patients with severe aortic valve disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
309
1
28

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 478 publications
(347 citation statements)
references
References 34 publications
9
309
1
28
Order By: Relevance
“…11-13,31- 33 Azevedo et al have shown significantly worse long-term survival and LV functional improvement after aortic valve surgery for severe AS or AR in patients with ≥30% myocardial fibrosis measured by histopathology. 34 Corroborating those results, the present study demonstrated a significant correlation between DMF and LV mass. 12,31,32, 35 Patients with severe DMF also showed higher BNP levels than the patients with milder degrees of DMF.…”
Section: Conclusion and Clinical Implicationssupporting
confidence: 87%
“…11-13,31- 33 Azevedo et al have shown significantly worse long-term survival and LV functional improvement after aortic valve surgery for severe AS or AR in patients with ≥30% myocardial fibrosis measured by histopathology. 34 Corroborating those results, the present study demonstrated a significant correlation between DMF and LV mass. 12,31,32, 35 Patients with severe DMF also showed higher BNP levels than the patients with milder degrees of DMF.…”
Section: Conclusion and Clinical Implicationssupporting
confidence: 87%
“…86 A new superparamagnetic iron oxide probe conjugated to recombinant human annexin has demonstrated diffuse myocardial signal loss in rats treated with doxorubicin, suggestive of apoptosis by CMR. 87,88 Myocardial fibrosis detected as delayed enhancement (DE) by CMR has proven prognostic value in coronary heart disease, 89 and restrictive myocardial diseases including aortic stenosis, 90 hypertrophic cardiomyopathy, 91,92 and the infiltrative diseases of sarcoidosis 93 and amyloidosis. 94 CMR studies in larger populations of patients receiving potentially cardiotoxic agents are needed to see whether the presence of fibrosis detected by gadolinium enhancement identifies a cohort of patients more vulnerable to the cardiotoxic effects of chemotherapy, who may benefit from more frequent and long-term follow-up, and earlier treatment with ACE inhibitors and beta blockade to reduce the incidence and severity of chemotherapy-induced heart failure.…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%
“…Several recent studies measured myocardial fibrosis in this specific population, showing that its presence (identified by late gadolinium enhancement on myocardial MRI) was associated with reduced postoperative survival and its absence with significant postoperative improvement in LVEF and NYHA score [25,26]. Complementary myocardial exploration would therefore be interesting in this population in order to explore the implication of diastolic dysfunction in post-TAVI PH.…”
Section: Myocardial Fibrosis?mentioning
confidence: 99%